Post-traumatic stress disorder and coping styles of war veterans from Tuzla Canton twenty years after the war - Zihnet Selimbašić; Maja Brkić; Nermina Kravić; Jasmin Hamidović; Mirna Selimbašić (Medicinski glasnik, 2017)
Aim: To analyse symptoms of posttraumatic stress disorder and coping strategies of war veterans in Tuzla Canton twenty years after the war in Bosnia and Herzegovina (B&H). Methods: The study analysed a group of 120 war veterans from the Tuzla Canton who had experience of the war in B&H. For assessment of posttraumatic stress disorder Harvard Trauma Questionnaire was used, a version for Bosnia and Herzegovina and for assessment of coping styles Life Style Index was used. Results: Concerning number of traumatic experiences of war veterans, it was found that they suffered 12 traumatic experiences. Most often traumatic experience was the participation in fighting and shelling (90.0%), knowledge of injuries in combat or landmine injuries of family members or friends (75.8%), exposure to snipers (74.2%). The most important were the symptoms of numbnessemotional numbness (2.62%), the symptoms of intrusion (2.58%) and the severity of the symptoms of PTSD (2.39%). The most common strategy of dealing with veterans of war was a projection (68.31%) and intellectualisation (56.20%). Conclusion: War veterans have experienced polytraumatic experiences in war and show increased expression of symptoms of posttraumatic stress disorder, emphasised psychosocial problems with a common defence mechanism in the form of projections twenty years after the war. War veterans are in need of continuous treatment in order to reduce long-term consequences of war trauma.
Keywords: war traumatisation; coping; Bosnia and Herzegovina